Tibetan Buddhism and personality. A qualitative study of the subjetive impact of buddhism in the personality and future anxiety of practitioners from Uruguay - Apud , Ismael (2024)
Uruguay. Previously, in a quantitative and cross-sectional study, we compared 52 Tibetan Buddhists with religious and non-religious population, showing significantly lower differences for Future Anxiety, Aggression-Hostility and Activity, when comparing the Buddhist group with the rest, and in Neuroticism-Anxiety when compared only with the religious group. The current article shows the qualitative results of the project, with a sample of 14 Buddhists. In-depth interviews were used to explore participants’ perception of psychological changes attributed to Buddhism. The qualitative analysis converged in certain results when compared to the quantitative counterpart. The results describe participants’ perception of changes in constructs/facets related to Aggression-Hostility, Future Anxiety and Neuroticism-Anxiety. The analysis of the constructs Activity and Sociability-Extraversion allowed to a better comprehension of Tibetans’ “ascetic” profile. Regarding the divergences between both qualitative and quantitative studies, although the constructs related to Sensation Seeking-Impulsivity were not significant in the previous quantitative study, in this qualitative part they acquired special relevance. In order to understand these changes, and following the practitioners’ narratives, we searched for relationships between the psychological constructs studied and the religious dimensions of “belief”, “practice” and “belong”. Buddhist beliefs were especially considered as interpretative frameworks that provide a greater perception of control around daily life problems. The meditative practice was perceived as a space for psychological transformation. Finally, the community was understood as a supportive network for the practice and transmission of Buddhism.